Growth, Development and Survival Rate of The Blue Swimming Crab (Portunus pelagicus) Cultured using Different Larvae Feeds - Rabby, Ahmad Fazley; Rahman, Turabur; Islam, Zahidul; Hasan, Jakia; Aktaruzzaman, Md; Rahman, Shafiqur; Karim, Ehsanul; Ali, Md Zulfikar (Marine Science Department Diponegoro University, 2024)
Blue swimming crab (Portunus pelagicus) is one of the most important commodities of softshell industry. Besides mud crab its demand as feed is increasing day by day. As a coastal dominant country, Bangladesh has a great feasibility of this species in culture, production, use and export. However, the production contribution from Bangladesh is still from natural sources and far behind in terms of farming, culture and production. Optimization of larval rearing techniques is therefore important to develop intensive hatchery rearing technique for this species. So, this study is aimed to develop larvae production technique of Portunus pelagicus with a better survival rate. Newly hatched first zoeal of Portunus pelagicus were reared using three different diets till second zoeal stage: (Treatment 1= Artemia franciscana umbrella + Rotifer (Brachionus rotundiformis); Treatment 2= Rotifer (B. rotundiformis) and Treatment 3= Artemia franciscana umbrella). Then, Artemia franciscana nauplii were used for all three treatments till they metamorphosed to crab instar. Regularly, water quality parameters were monitored and maintained and the survival and molting to next stages was observed. The result showed that, all the hatched zoea of P. pelagicus could successfully turns into crab instar stage under all the treatment applied, but the highest survival rate 6.08% was found in case of treatment 2 followed by 0.58%, 0.91%, respectively in treatment 1 and 3. In terms of metamorphosis, it took more than 15 and 14 days respectively from zoea 1 to metamorphose into megalopa for treatments 1 and 3, whereas metamorphosis from zoea 1 to megalopa in treatment 2 finished at the 12th day with a higher Larval Stage Index (LSI) value which was 4.9. Finally, at the 15th day larvae were metamorphosed into crablet for treatment 2 and 18 and 16 days required for metamorphosis into crablets for treatment 1 and 3, respectively. However, the larval feed showed a significant effect on growth and survival of P. pelagicus larvae, whereas the earlier larval stage of P. pelagicus rearing with Rotifer (B. rotundiformis) is found as the most suitable diet.